Synthesis of silane‐grafted ethylene vinyl acetate copolymer and its application to compatibilize the blend of ethylene‐propylene‐diene copolymer and silicone rubber. Issue 5 (20th April 2017) - Zhang, Weijian; Yan, Wei; Pan, Renjie; Guo, Weihong; Wu, Genhua
Abstract : Vinyltrimethoxysilane‐grafted ethylene vinyl acetate copolymer (EVA‐g‐VTMS) was synthesized and applied to compatibilize ethylene‐propylene‐diene copolymer (EPDM)/methyl vinyl silicone rubber (MVQ) blends. The silane‐grafting was successfully proved by differential scanning calorimetry, FTIR spectroscopy and XPS spectroscopy. The additive amount of the compatibilizer (EVA‐g‐VTMS) was optimized to be 10 phr (parts per hundred of rubber in weight) based on analysis of scanning electron microscopy, mechanical properties, aging properties, dynamic mechanical properties, rheological properties and thermal properties. Compared with the blend without EVA‐g‐VTMS, results show that the blend with 10 phr of EVA‐g‐VTMS exhibits the finest morphology. Tensile strength, elongation at break, modulus at 100% elongation, tear strength and TE index increase by 82.5%, 16.9%, 60.0%, 40.9%, and 41.9%, respectively. Dynamic mechanical analysis reveals storage modulus increase and glass transition temperatures of EPDM and MVQ move closer to each other. Rheological analysis shows a decrease in complex modulus and complex viscosity, and the processibility of the blend was improved. Furthermore, thermogravimetric analysis shows enhancement of thermal stability. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers